PERANAN GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKANKEDISIPLINAN BELAJAR SISWA - Afiatin Nisa (Universitas Indraprasta PGRI, 2016)
The purpose of this research is to find out The Role Of Counselling Teacher in Developing The Discipline of Students Learning at MTs Ar Rahmah East Jakarta, by using qualitative method with descriptive approach. The source of the data in this research is the headmaster, counseling teacher,and grade VII of 80 students through purposive sampling technique. Research Instrument used in this research are questionnaire, interview, and observation. Questionnaire filled out by students, interviewis done for headmaster and counseling teacher and observation is used in observing the school environment. The conclusion of the research is there are a Very Strong Category in The Role Of Counselling Teacher in Developing The Discipline of Students Learning at MTs Ar Rahmah EastJakarta.Keyword: The Role of Counselling, The Discipline of Student Learning